Non-invasive multimodal optical coherence and photoacoustic tomography for human skin imaging. Issue 1 (December 2017) - Chen, Zhe; Rank, Elisabet; Meiburger, Kristen; Sinz, Christoph; Hodul, Andreas; Zhang, Edward; Hoover, Erich; Minneman, Micheal; Ensher, Jason; Beard, Paul; Kittler, Harald; Leitgeb, Rainer; et al.
Abstract The cutaneous vasculature is involved in many diseases. Current clinical examination techniques, however, cannot resolve the human vasculature with all plexus in a non-invasive manner. By combining an optical coherence tomography system with angiography extension and an all optical photoacoustic tomography system, we can resolve in 3D the blood vessels in human skin for all plexus non-invasively. With a customized imaging unit that permits access to various parts of patients' bodies, we applied our multimodality imaging system to investigate several different types of skin conditions. Quantitative vascular analysis is given for each of the dermatological conditions to show the potential diagnostic value of our system in non-invasive examination of diseases and physiological processes. Improved performance of our system over its previous generation is also demonstrated with an updated characterization.